Green approach of synthesis of thiazolyl imines and their impeding behavior against corrosion of mild steel in acid medium - Singh A.K.; Chugh B.; Thakur S.; Pani B.; Lgaz H.; Chung I.-M.; Pal S.; Prakash R. (My University, 2025)
Recent advancements regarding synthetic methods of organic molecules, viz. conventional method, and exposure of microwave as well as ultrasound waves led us to synthesize four different thiazolyl imines by different methods like conventional heating and by exposure of ultrasound waves to the mixture of reactants. Ultrasonication was found more efficient, fast and clean method of the synthesis of thiazolyl imines. The synthesized compounds were employed to overcome metallic corrosion problem in various industries, as application of corrosion inhibitor has been a subject of research these days. In view of this, the present work deals with the comprehension of the greener synthetic route for thiazolyl imines and employing those as corrosion inhibitors for investigating acidic corrosion of mild steel using electrochemical, gravimetric, surface and theoretical studies. The thiazolyl imines were found to impede acid corrosion of mild steel (MS) by adsorbing themselves as per Langmuir isotherm. The effect of their adsorption on the surface morphology of MS was studied on micro/nano level using scanning electron microscopy/atomic force microscopy, X-ray spectroscopic studies, viz. energy dispersive X-ray microanalysis (EDXMA) and X-ray photoelectron spectroscopy (XPS), subsequently explaining their adsorption mechanism. The theoretical parameters obtained from computational study of inhibitor molecules explained the experimental findings extremely well. © 2020 Elsevier B.V.